Tinjauan Hukum Islam terhadap Tutup Kandungan Wanita dengan Alasan Pembatasan Keturunan (Kajian Perspektif Maslahah): Review of Islamic Law on Covering a Woman's Womb for the Reason of Restricting Heredity (Maslahah Perspective Study) - Sam, Zulfiah; Santi Sarni; Nabilah Al Azizah (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2022)
This research aims to determine Islamic law regarding the closure of a woman's womb for reasons of limiting offspring (maslahah perspective study). This research uses a type of library study research, which focuses on the study of manuscripts and texts, using historical, normative and philosophical approach methods. The results of the research found are as follows: First, the concept of uterine closure or tubectomy according to health science, uterine closure is a process which is carried out by blocking the uterine tubes (fallopian tubes) to prevent the transfer of ovum to the uterine cavity and is achieved by cutting the tube, installing a clip or ring. In this process there are several impacts that will arise, there are short-term impacts that will be felt after the tubectomy process is carried out and also long-term impacts that will not be immediately felt by the woman who has the tubectomy or closure of the womb. Second, the view of Islamic law regarding the closure of a woman's womb for the reason of limiting heredity is that it is not permissible to cover the womb because it is contrary to human nature and also to Islamic law which has been established by Allah SWT. has appointed his servant with the best determination. Third, the Islamic view of covering a woman's womb for the reason of limiting offspring seen from the perspective of maṣlaḥah is contrary to maslahah itself. Because the purpose of enacting Islamic law is to benefit its adherents, it also maintains the goals of the law and prevents harm and closure of women's wombs, which is contrary to the goal of maṣlaḥah itself.